Metabolic trajectories of diabetic ketoacidosis onset described by breath analysis - Awchi, Mo; Singh, Kapil Dev; Brenner, Sara Bachmann; Burckhardt, Marie-Anne; Hess, Melanie; Zeng, Jiafa; Datta, Alexandre N.; Frey, Urs; Zumsteg, Urs; Szinnai, Gabor; Sinues, Pablo (Frontiers in Endocrinology, 2024)
Purpose This feasibility study aimed to investigate the use of exhaled breath analysis to capture and quantify relative changes of metabolites during resolution of acute diabetic ketoacidosis under insulin and rehydration therapy. Methods Breath analysis was conducted on 30 patients of which 5 with DKA. They inflated Nalophan bags, and their metabolic content was subsequently interrogated by secondary electrospray ionization high-resolution mass spectrometry (SESI-HRMS). Results SESI-HRMS analysis showed that acetone, pyruvate, and acetoacetate, which are well known to be altered in DKA, were readily detectable in breath of participants with DKA. In addition, a total of 665 mass spectral features were found to significantly correlate with base excess and prompt metabolic trajectories toward an in-control state as they progress toward homeostasis. Conclusion This study provides proof-of-principle for using exhaled breath analysis in a real ICU setting for DKA monitoring. This non-invasive new technology provides new insights and a more comprehensive overview of the effect of insulin and rehydration during DKA treatment.